Do Exact Calculation and Computation Estimation Reflect the Same Skills? Developmental and Individual Differences Perspectives - Ganor-Stern, Dana (Frontiers in Psychology, 2018)
Groups of children in 4th, 5 th, and 6 th grades and college students performed exact calculation and computation estimation tasks with two-digit multiplication problems. In the former they calculated the exact answer for each problem, and in the latter they estimated whether the result of each problem was larger or smaller than a given reference number. The analyses of speed and accuracy both showed different developmental patterns of the two tasks. While the accuracy of exact calculation increased with age, at least from 4th to 6th grade, the accuracy of the estimation task reached its maximum level already in 4th grade and did not change with age. The reaction time of the exact calculation task was longer than that of the estimation task. The reaction time for both tasks remained constant in childhood and decreased in adulthood. Importantly, the improvement in speed in adulthood was larger for the exact calculation task. Similarly, within group variability in accuracy was larger in the exact calculation task than in the computation estimation task. Thus, the developmental data and the individual differences analysis suggest that they reflect at least in part different skills. Support for this idea is provided by the low correlation between the accuracy of the two tasks.